SOD1-related ALS with anticipation in a large family from Martinique. Issue 7 (2nd October 2021) - Giguet-Valard, Anna-Gaelle; Bellance, Rémi; Jeannin, Séverine; Duclos, Sophie; Olive, Pascale; Allard-Saint-Albin, Oriane; Cazeneuve, Cécile; Clot, Fabienne; Sophie, Pittion-Vouyovitch; Barnetche, Thomas; Smith-Ravin, Juliette; Goizet, Cyril
Abstract: Amyotrophic Lateral Sclerosis (ALS) is a rare neurological disorder that causes degeneration of upper and lower motor neurons and their axons. ALS is mostly sporadic, but there are familial forms. In more than half of the familial forms, a pathogenic variant is found in one of the following genes: C9ORF72, SOD1, TDP-43, FUS, and VCP . SOD1 is the 2nd most common gene involved in genetic forms of ALS. Genotype–phenotype relationships are occasionally established in genetic forms of ALS associated with SOD1 mutations pathogenic variants. The c.281G > T (p.[G93V]) variant in SOD1 is associated with a rarely described and unexplained anticipation phenomenon. We report a large family from Martinique in whom ALS is associated with a c.281G > T (p.[G93V]) pathogenic variant in SOD1 and a statistically suggested anticipation. A whole-exome study and detection of CNVs (CoDESeq) from 3 affected members of this family revealed the presence of variants of uncertain signification (VUS) in other ALS genes. VUS in DCTN1 and NEFH were present in patients of the 2nd generation, and CNVs involving UBQLN2 and C21orf2 were found in the youngest case of the family.